مدى توافق مناهج قسم المحاسبة مع معيار التعليم الدولي رقم (2) التطوير المهني الأولي الكفاءةالفنية - سالم, عبد الوهاب (جامعة الوادي University of Eloued, 2020)
هدفت هذه الدراسة الى بيان مدى توافق مناهج قسم المحاسبة بمرحلة البكالوريوس بجامعة السيد محمد بن على السنوسي الاسلامية مع معيار التعليم الدولي رقم (2) التطوير المهني الأولي )الكفاءة الفنية(. ومن اجل تحقيق هدف الدراسة فقد تم مقارنة المجالات الرئيسة وموضوعاتها الفرعية كما جاءت في معيار التعليم الدولي رقم (2) التطوير المهني الأولي (الكفاءة الفنية). مع مناهج قسم المحاسبة بجامعة السيد محمد بن على السنوسي الاسلامية طبقا لأخر توصيف لمفردات المواد الدراسية بالقسم . وبعد اجراء المقارنة اظهرت النتائج ان مجالات المحاسبة الادارية و التمويل والضرائب والادارة المالية والقانون التجاري واللوائح والاقتصاد تتوافق مع مناهج مواد القسم . وان مجالات المحاسبة المالية والتقارير والمراجعة وخدمات التأكيد و الحوكمة وادارة المخاطر والرقابة الداخلية والاعمال والبيئة التنظيمية تتوافق الى حد ما مع مناهج مواد قسم المحاسبة بالجامعة وعدم توافق مجال الادارة المالية مع منهج قسم المحاسبة بالجامعة. This study aimed to demonstrate the compatibility of the zurricula of the Department of Accounting at the undergraduate stage at The Islamic University of Asaied Mohamed Bin Ali Al Sanussi with the international education standard No. (2) Initial Professional Development – Technical Competence (Revised).. International Education Standard No. (2) Initial Professional Development – Technical Competence (Revised). With the curricula of the Accounting Department at The Islamic University of Asaied Mohamed Bin Ali Al Sanussi, according to the latest descriptions of the vocabulary of the department’s subjects.After conducting the comparison, the results showed that the areas of administrative accounting, finance, taxation, financial management, commercial law, regulations, and economics are consistent with the curricula of the department’s materials. The areas of financial accounting, reports, auditing, confirmation services, governance, risk management, internal control, business and the regulatory environment are to some extent compatible with the curricula of the university’s accounting department and the financial administration’s field inconsistency with the university’s accounting department’s approach.
The extent of compatibility of the accounting department curricula with international education standard No. (2) initial professional development A case study at The Islamic University of Asaied Mohamed Bin Ali Al Sanussi
مقال
Keywords: منهج قسم المحاسبة، معيار التعليم الدولي رقم (2) التطوير المهني الأولي )الكفاءة الفنية) ، التعليم المحاسبي.; Keywords: Accounting Department Curriculum, International Education Standard No. (2) Initial Professional Development – Technical Competence (Revised). , Accounting Education: XN2، XN1.